Determinants of Vegetarianism and Partial Vegetarianism in the United Kingdom - LEAHY, EIMEAR; TOL, RICHARD S. J.; LYONS, SEAN (ESRI)
Vegetarianism is increasing in the western world. Anecdotally, this trend can be attributed to heightened health, environmental and animal welfare concerns. In this paper we investigate the factors associated with vegetarianism among adults and children in the UK. Using the 2008 Health Survey for England, we use a logit model to assess the relationship between vegetarianism and the socioeconomic and personal characteristics of the respondents. We also analyse the factors associated with varying levels of meat consumption using an ordered logit model. This paper adds to the existing literature as it is the first paper to estimate the determinants of vegetarianism using a large dataset containing individual level consumption data.
PUBLISHED
Keywords: children; consumption; data